2011
DOI: 10.1111/j.2041-210x.2010.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for collaboratively identifying research priorities and emerging issues in science and policy

Abstract: Summary1. There is a widely recognized gap between the data generated by researchers and the information required by policy makers. In an effort to bridge the gap between conservation policy and science, we have convened in several countries multiple groups of policy makers, practitioners and researchers to identify priority information needs that can be met by new research in the social and natural sciences. 2. The exercises we have coordinated included identification of priority policy-relevant research ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
371
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 319 publications
(381 citation statements)
references
References 27 publications
2
371
0
8
Order By: Relevance
“…We applied a four-step participatory method based on the ecological or conservation research priority-setting exercise described by Sutherland et al (2011). During these steps a broad range of research questions were identified and collated by the potential users of the research results (policy makers, natural resource managers working for the state, private or NGO sectors), then prioritized by participants of a stakeholder workshop.…”
Section: Methodsmentioning
confidence: 99%
“…We applied a four-step participatory method based on the ecological or conservation research priority-setting exercise described by Sutherland et al (2011). During these steps a broad range of research questions were identified and collated by the potential users of the research results (policy makers, natural resource managers working for the state, private or NGO sectors), then prioritized by participants of a stakeholder workshop.…”
Section: Methodsmentioning
confidence: 99%
“…To identify the research questions we used the Priority Setting Exercise method established by Sutherland et al (2006), described in Sutherland et al (2011) and modified by Sutherland et al (2013). This brought together a working group of participants in a transparent, collaborative and democratic manner, to reduce an initial, long and unfiltered list of candidate questions through a multistage participatory process to a final, short and democratically agreed list.…”
Section: Methodsmentioning
confidence: 99%
“…The last national census was in 2010 when the population was recorded Sutherland et al (2006), described in Sutherland et al (2011) and modified by Sutherland et al (2013) followed for the generation of the research questions and the prioritisation process to obtain the 50 priority environmental research questions for Galápagos.…”
Section: Developmentmentioning
confidence: 99%
“…The listing exercise was conducted by email using established processes for collecting the expertise of a group of experts (Sutherland et al 2011a). We selected a group of experts with extensive knowledge of a range of aspects of ecosystem service research and management.…”
Section: Methodsmentioning
confidence: 99%